Detection and Sizing of Surface Flaws With a SQUID-Based Eddy Current Probe - Moulder, J. C. (J Res Natl Bur Stand (1977), 1987)
In a new approach to eddy current detection and sizing of surface-breaking flaws, we have coupled a conventional reflection probe to a superconducting quantum interference device (SQUID) to produce an eddy current probe with increased sensitivity and signal to noise ratio. The reflection probe consists of an air-core excitation coil surrounding two counterwound ferite-core pickup coils connected in series. A room-temperature probe is inductively coupled to a SQUID, which operates in a liquid helium bath. The new probe was used to obtain flaw signals from a number of electrical-discharge machined slots in aluminum alloy 6061. Results indicated that by scanning the probe along the length of the flaw, the length could be determined from the extent of the flaw signal. The peak amplitude of the flaw signal was found to be proportional to the cross-sectional area of the flaw. Empirical calibration curves relating these quantities were used to invert successfully the experimental data obtained for the EDM slots.